Motivations, Monitoring Technologies, and Pay for Performance - Cordella, Antonio; Cordella, Tito (World Bank Group, Washington, DC, 2014)
Monitoring technologies and pay for performance contracts are becoming popular solutions to improve public services delivery. Their track record is however mixed. To show why this may be the case, this paper develops a principal agent model where agents' motivations vary and so does the effectiveness of monitoring technologies. In such a set-up the model shows that: (i) monitoring technologies should be introduced only if agents' motivations are poor; (ii) optimal pay for performance contracts are nonlinear/non-monotonic in agents' motivations and monitoring effectiveness; (iii) investments aimed at improving agents' motivations and monitoring quality are substitutes when agents are motivated, complements otherwise; and (iv) if the agents' "type" is private information, the more and less motivated agents could be separated through a menu of pay for performance/non pay for performance contracts, such that only the less motivated choose the pay for performance ones.